Theopoetics, An Impossible Epistemology? Considerations for a Fundamental Theology - Meléndez, Luis Gustavo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
This paper examines the origins and development of theopoetics as a movement in a clear process of consolidation in which, we can find out certain elements that suggest that it is not only an academic trending topic but a theological method itself, with a considerable autonomy. Therefore, throughout this work, we try to clarify its epistemological assumptions and the conditions of possibility that allow establishing the veracity and relevance of the theopoetics approach. In this work we will focus on theopoetics as a method to address the relationships between theology and literature.
Keywords: theopoetics; theological-epistemology; poiesis; poetic-reason; theological aesthetics; literature; fundamental theology